Mapping COVID-19: How web-based maps contribute to the infodemic. Issue 2 (July 2020) - Mooney, Peter; Juhász, Levente
A proliferation of web-based maps have appeared depicting many different aspects of the spread of the novel coronavirus (SARS-CoV-2). In this commentary, we consider the usage of web-based mapping during the COVID-19 pandemic and argue that web maps have been widely misused for delivering public information on this fast moving, epidemiologically complex, and geographically unbounded process.